Impact of Maternal Education on Child Mortality - Khurshid, Zamurd; Siddique, Humaira; Waqas, Ali; Sabir, Shinza (International Journal of Social Sciences and Management, 2019)
The purpose of study was to investigate the impact of maternal education on child mortality. A large frame of studies suggests that a causal relationship exists between maternal training and youth mortality. This paper seeks to shed some light at the influence of maternal schooling and youth mortality. The results show that acquisition of education leads to higher human, social and cultural capital amongst moms, that's associated with progressed baby survival. Moreover, this study show that better training of the mother is related to more physical and choice-making autonomy for her inside the household, which may also lead to higher fitness outcomes for the child.